Frequency analysis of tangential force measurements on a vertical axis wind turbine. Issue 4 (September 2016) - Rossander, Morgan; Goude, Anders; Bernhoff, Hans; Eriksson, Sandra
Abstract: This paper presents experimental results of the torque ripple obtained from a three bladed 12 kW experimental H-rotor prototype. The measurements are performed by means of load cells installed on the base of the struts and by electrical measurements on the generator. The resulting torques are analysed in terms of frequency spectrum and order spectrum (synchronized with rotation). The measurements are compared to aerodynamic simulations of the turbine. The expected large torque ripple at three times the rotational speed (3 p) is only weakly represented at the hub and in the generator. This suggests that the system is filtering the ripple and/or that the simulations are overestimating the 3 p component. The torque ripple loads on the drive train are therefore lower than anticipated. Even if highly attenuated, most of the low frequencies correlating to aerodynamics are still represented in the generator electrical torque. Given a certain baseline, this opens for possible online monitoring of unbalances in the turbine by electrical measurements.